Methodological grounds of development of the Armed Forces of Ukraine from the economic point of view - Chernyshova, Iryna; Marko , Ivan; Skurinevska , Lesia; Yarmolenko , Olesia; Shevchuk , Oleksandr; Shepel, Denys (Social Development and Security, 2021)
The article presents a formalized model of the functioning of the state economy in the interests of the development of the Armed Forces of Ukraine. The transformation of economic power into military power does not occur automatically, but due to the implementation of military-economic relations, which are conditioned by the production links of society and are formed under the influence of political and military factors of the state. The main idea is that ensuring the high combat effectiveness of the Armed Forces of Ukraine and the state’s defense capabilities depends both on the peculiarities of the functioning of the state’s economy and on the validity of decisions and actions in the military sphere. In order to carry out economic preparation of the state for a possible war and high-quality economic support of military actions or modern wars, it is necessary to carry out a military-economic analysis of these processes. The main purpose of such an analysis should be, on the one hand, to identify patterns and trends in economic processes and economic activity at all levels of the military sphere, and on the other hand, to have a clear understanding of the necessary financial resources to support the Ukrainian Armed Forces. These resources include resources for armaments and military equipment, training of personnel, military infrastructure and expendable material and technical means, which will ensure the required level of combat effectiveness of troops (forces). With the beginning of the war there is an intensive use of defense products without sufficient reproduction. At this time, there may be a threat of economic collapse, as military consumption completely absorbs defense production and part of the previously accumulated national wealth. To avoid this situation, it is necessary to determine in advance the limits of such consumption, which in turn largely depend on the scale of economic power of the state and the required level of combat effectiveness of the Armed Forces of Ukraine.